PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT TERHADAP KEMAMPUAN MENULIS SURAT DINAS SISWA KELAS VII SMP NEGERI AIR SATAN - Julia, Clara; Nugroho, Agung; Sari, Inda Puspita (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
This study aims to determine the significant completion of the ability to write official letters through the Cooperative Script learning model in class VII students of SMP Negeri Air Satan. This thesis is entitled Application of the Cooperative Script Learning Model to the Ability to Write Official Letters of Class VII Students of SMP Negeri Air Satan. The formulation of the problem of this research is whether the application of the Cooperative Script learning model can significantly complete the ability to write official letters of class VII students of SMP Negeri Air Satan?. The research method used in this study is a quasi-experiment. The population is class VII students of SMP Negeri Air Satan in the 2024/2025 Academic Year with a sample of class VII A. Data collection was carried out using a test technique in the form of an official letter writing test and a non-test technique in the form of interviews. The collected test data were analyzed using the SPSS version 22 calculation t-test, the